Phytochemical and Cytotoxic Investigation of Codiaeum variegatum Linn. leaf (Stamford Journal of Pharmaceutical Sciences, 2011)
DOI: http://dx.doi.org/10.3329/sjps.v3i2.8039S.J. Pharm. Sci 3(2): 51-53